The Vibration Characteristics of Ground of Rock Blasting in Silt-Rock Strata - Tao Yin; Chuanbo Zhou; Changqing Zheng; Jugen Fu; Ziru Guo (Shock and Vibration)
As the shield section passes through the silt-rock strata, the rock stratum of the tunnel section has to be blasted into blocks in advance, and the diameter of the blocks should be less than 30 cm after breaking, and then, the blocks could smoothly enter the soil cabin through the opening of the tunnel boring machine (TBM) cutter head and finally be discharged through the screw machine. The geology of rock blasting in silt-rock strata is complex, and the vibrations caused by blasting threaten the safety of buildings around the blasting area. According to the measured data of blasting vibrations at the sites, the waveform duration of vibration acceleration and the distribution characteristics of dominant frequency of vibration velocity were analyzed, the energy characteristics of vibration velocity were researched by wavelet analysis, and the attenuation laws of vibration velocity were studied by dimensional analysis (DA). The dominant frequency bands of vibration energy of ground are in the range of 0–15.625 Hz, and the distribution characteristics of frequency bands of vibration energy in different directions of the ground are similar to each other, but the energy magnitude is different from each other. The research results could provide a reference for the safe blasting distance of buildings under similar geological conditions.